Framing immigrants as seekers of social benefits: the impact of the Great Recession at the family-level and the development of anti-immigrant anxieties - Fernández-Barutell, Luis (Trabajo Social Global-Global Social Work, 2019)
Substantial research has addressed the association between economic factors (e.g., employment rate) and perception of immigrants among the general public in the host societies. This study used the Transatlantic Trends Survey 2014 to examine whether the characterization of immigrants as social benefits seekers is related to one´s family financial situation being greatly affected by the Great Recession. We conducted a series of ordinal logistic regressions to compare three different geopolitical contexts, namely the United States, the Southern Europe region, and the triad France-Germany-United Kingdom. Our results confirmed that framing immigrants as social benefits seekers is indeed related to one´s family being greatly impacted by the Great Recession. Significantly, the direction of such association varies among contexts, as those greatly impacted by the crisis in Southern Europe showed lower odds of framing immigrants as social benefits seekers, while the opposite happening in both the United States and the triad France-Germany-United Kingdom. Recommendations for practice and research are discussed.